Improving Tajwid Understanding through Problem Based Learning in Grade VII Qur'an-Hadith at MTs Nurul Iman Berbak - Muhammad Nuril Huda, Nispi Syahbani (Journal of Educational Studies, 2025)
This study aimed to describe the process of learning tajwid rules using the Problem Based Learning (PBL) model and to determine its effectiveness in improving Grade VII students' understanding at MTs Nurul Iman Berbak, particularly regarding the rules of nun sakinah and tanwin. This was a classroom action research study following the Kemmis and Mc. Taggart model, conducted over two cycles consisting of planning, acting, observing, and reflecting. The research subjects were 21 Grade VII students, comprising 10 male and 11 female students. Data were collected through observation, interviews, documentation, and oral tests, then analysed both qualitatively and quantitatively using percentage formulas. The results showed that PBL implementation increased students' average reading score from 58.1 in the pre-cycle to 70.5 in Cycle I, and to 85.7 in Cycle II, with mastery rates rising from 33% to 90.5%. Improvements were also observed in teacher and student activity, rising from 72% to 88% and from 68% to 86%, respectively. Based on these findings, it was concluded that the Problem Based Learning model effectively improved students' understanding of tajwid rules and is a viable alternative model for Qur'an-Hadith instruction in madrasah settings.